The Ethics of Species : An Introduction / [electronic resource] - Sandler, Ronald L. (Cambridge : Cambridge University Press, 2012)
We are causing species to go extinct at extraordinary rates, altering existing species in unprecedented ways and creating entirely new species. More than ever before, we require an ethic of species to guide our interactions with them. In this book, Ronald L. Sandler examines the value of species and the ethical significance of species boundaries and discusses what these mean for species preservation in the light of global climate change, species engineering and human enhancement. He argues that species possess several varieties of value, but they are not sacred. It is sometimes permissible to alter species, let them go extinct (even when we are a cause of the extinction) and invent new ones. Philosophically rigorous, accessible and illustrated with examples drawn from contemporary science, this book will be of interest to students of philosophy, bioethics, environmental ethics and conservation biology.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Environmental ethics; Bioethics; Species; Biodiversity